CAREER GROWTH AND WORK ENVIRONMENT IN REDUCING TURNOVER INTENTION: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT - Rachel Veronica; Gogor Arif Handiwibowo (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
This study aims to examine the effects of physical work environment, career growth, and family supportive organization on turnover intention, with employee engagement as a mediating variable among contract employees in a mining contractor company. Using a quantitative cross-sectional survey design, data were collected from 235 respondents selected through stratified sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that physical work environment and career growth have positive and significant effects on employee engagement and negative effects on turnover intention. In contrast, family supportive organization does not show a meaningful effect on either employee engagement or turnover intention. Employee engagement is also found to partially mediate the relationships between physical work environment and turnover intention, as well as between career growth and turnover intention. Among the examined predictors, career growth emerges as the most dominant factor in reducing employees’ intention to leave the organization. These findings indicate that strengthening career development opportunities and improving the quality of the physical work environment are critical for retaining contract employees in the mining sector. Theoretically, this study extends the application of social exchange theory by demonstrating the role of employee engagement as a psychological mechanism linking organizational practices to employee retention in a high-risk work setting.